Boosting Water Oxidation through In Situ Electroconversion of Manganese Gallide: An Intermetallic Precursor Approach. Issue 46 (15th October 2019) - Menezes, Prashanth W.; Walter, Carsten; Hausmann, Jan Niklas; Beltrán‐Suito, Rodrigo; Schlesiger, Christopher; Praetz, Sebastian; Yu. Verchenko, Valeriy; Shevelkov, Andrei V.; Driess, Matthias
Abstract: For the first time, the manganese gallide (MnGa4 ) served as an intermetallic precursor, which upon in situ electroconversion in alkaline media produced high‐performance and long‐term‐stable MnOx ‐based electrocatalysts for water oxidation. Unexpectedly, its electrocorrosion (with the concomitant loss of Ga) leads simultaneously to three crystalline types of MnO x minerals with distinct structures and induced defects: birnessite δ‐MnO2, feitknechtite β‐MnOOH, and hausmannite α‐Mn3 O4 . The abundance and intrinsic stabilization of Mn III /Mn IV active sites in the three MnO x phases explains the superior efficiency and durability of the system for electrocatalytic water oxidation. After electrophoretic deposition of the MnGa4 precursor on conductive nickel foam (NF), a low overpotential of 291 mV, comparable to that of precious‐metal‐based catalysts, could be achieved at a current density of 10 mA cm −2 with a durability of more than five days. Abstract : Partnership in action : Electrocorrosion and concomitant leaching of gallium from the structurally compelling intermetallic manganese gallide MnGa4 lead to a highly active electrocatalyst system for water oxidation in alkaline media. Under the electrochemical reaction conditions, three distinct crystalline and highly active MnOx phases result simultaneously with considerably low overpotentials and durability of over five days.